Exercise-induced bronchospasm among healthy elite cross country skiers and non-athletic students - Pohjantähti, H.; Laitinen, J.; Parkkari, J. (Scandinavian Journal of Medicine & Science in Sports, 2005)
Regular exercise in cold, dry air is believed to be a predisposing factor for exercise-induced bronchospasm (EIB). The aim of this study was to compare the occurrence of EIB among previously healthy elite cross country skiers and their non-athletic control subjects.